The Indonesian economic crisis implies immense changes in the forest sector - Sunderlin, William D. (Center for International Forestry Research, 1998)
The economic crisis unfolding in Indonesia since mid-1997 has led to profound socioeconomic and policy changes that are affecting the forest sector and land use in general. In this paper we document some of these changes and speculate about possible consequences for forest conservation and management, drawing largely on media reports and on general knowledge about the effects of macroeconomic change in developing countries. Our observations are preliminary and tentative, because as yet there are few data and research results available on the effects of the crisis. This is the third iteration of this paper. It will be revised and updated approximately every two to three months. The paper is structured as follows. We first describe the background of the economic crisis, and then discuss eight different effects of the economic crisis on the forest sector. These include: direct effects on the timber sector; indirect effects through the agricultural sector, transmigration, poverty and spontaneous migration, mining, and road construction; policy changes; and joint effects of the drought, fires, and the crisis.